Neogene–Quaternary tectonic, eustatic and climatic events shaped the evolution of a South American treefrog - Abreu-Jardim, Tatianne Piza Ferrari; de Lima, Natácia Evangelista; Jardim, Lucas; Maciel, Natan Medeiros; de Magalhães, Rafael Félix; Colli, Guarino Rinaldi; Haddad, Célio Fernando Baptista [UNESP]; Collevatti, Rosane Garcia (Wiley, 2023)
Aim: Understanding how past geological and climatic events could have generated intraspecific genetic variation at different temporal and spatial scales in the Neotropics requires a model encompassing distinct ecoregions. Because Anura species have their evolutionary history affected by climate and environmental changing, it is a suitable model to investigate the signatures of Neotropical historical events in species populations. Here we used a treefrog species to test hypotheses associated with tectonic, eustatic and climatic events along with isolation-by-environment and isolation-by-distance spatial patterns in genetic diversity. Taxon: Scinax squalirostris (Lutz, 1925), Anura: Hylidae. Location: Atlantic Forest, Cerrado, Chaco, Uruguayan Savanna and Pampas ecoregions in South America. Methods: We sequenced nuclear and mitochondrial data from 219 individuals of S. squalirostris sampled at 26 locations in South America. We performed statistical phylogeographic analyses and reconstruction of spatiotemporal dispersal dynamics. Ecological niche modelling was conducted to predict spatial changes in environmental suitability from the Last Glacial Maximum to the Holocene and present day. Results: We recovered a significant phylogeographic break roughly dated back to the Miocene (~7.6 Ma), coinciding with the retraction of marine incursions in the Paraná basin. Most dispersal events occurred in cooler periods of the Pliocene–Pleistocene transition. The spatial pattern in genetic diversity was not correlated with geographical distance or environmental variables. Main Conclusions: Scinax squalirostris had a quasi-stable distribution through time. Neogene–Quaternary tectonic, eustatic and climatic events drove the demographic history and dispersal dynamics of species, with a phylogeographical break dated to the Miocene coinciding with retractions of marine incursions in the Paraná basin. Lineage dispersal spread from the southern Atlantic Forest and retrieved gene flow signals congruent with the cold periods of the Pliocene and Pleistocene.
Keywords: Anura; coalescent simulation; ecological niche modelling; phylogeography; relaxed random walk model; Scinax squalirostris